The Effect of Tax Knowledge and Tax Sanctions on Individual Taxpayer Compliance (A Case Study at KPP Pratama Pondok Aren) - Putri, Azizah Setia; Asmonah, Siti (Jurnal Multidisiplin Sahombu, 2025)
Individual taxpayer compliance is a crucial factor in supporting the sustainability of state revenue. An optimal level of compliance is influenced not only by the tax administration system but also by taxpayers’ understanding of tax regulations and their perceptions of the sanctions imposed. This study aims to analyze the effect of tax knowledge and tax sanctions on individual taxpayer compliance at the Pondok Aren Primary Tax Office. A quantitative research approach with a survey method was employed. Data were collected through questionnaires distributed to registered and active individual taxpayers. Data analysis was conducted using multiple linear regression techniques to examine the relationships among the research variables. The results indicate that tax knowledge has a positive effect on individual taxpayer compliance. In addition, tax sanctions are also proven to have a significant effect in enhancing the level of compliance. These findings suggest that improving the quality of tax education and ensuring consistent enforcement of tax sanctions can promote sustainable taxpayer compliance behavior.